Human Movement Detection System Based on the Internet of Things - Syah, Nur Ifan; Sunardi, Sunardi (Universitas Ahmad Dahlan, 2024)
This research refers to making an IoT-based movement system tool. This system is used to calculate the number of human movements entering a room and also people leaving the room. In this study, a Passive Infrared Receiver (PIR) sensor is used to detect the movement of people when entering a room. The sensor will trigger a calculation of the number of people passing through the device, equipped with NodeMCU ESP 8266 as a microcontroller, with NodeMCU ESP 8266 it is more efficient to connect to the WiFi module on the Internet of Things system without the need for other modules. The tool is also equipped with an LED light as a notification of movement, an indicator buzzer if the room is fully filled, and there is also a Liquid Crystal Display (LCD) which is used to display the number of human movements entering and leaving the room, as well as the people who are in the room. The sensitivity of the PIR sensor depends on the distance of the object to the sensor. The research is running well. Notifications from the LED light go according to their duties, if someone enters the room then LED 1 will light ON, and if someone leaves the room then LED 2 will light ON. The results of the application in detecting objects of people or visitors one by one are conditioned based on walking movements and based on a person's height posture from 150 cm to 170 cm the accuracy of the object is accurate, because the distance from the object to the The tool is not too far so the tool can easily detect its movement.